Detection of Genetic Diversity in Four Candidate Genes by Polymerase Chain Reaction-Single Strand Conformation Polymorphism (PCR-SSCP) Analysis of Goats in Sri Lanka - Ariyarathne, H.B.P.C.; Lokugalappatti, LGS; Ariyaratne, H.B.S.; Munasinghe, D.M.S. (International Journal of Applied Sciences and Biotechnology, 2016)
Genetic diversity of Sri Lankan goats (Capra hircus) was evaluated using Polymerase Chain Reaction-Single Strand Conformation Polymorphism (PCR-SSCP) method to detect polymophism in four candidate genes (LALBA, k-CSN3, GnRHR and BMP4) in a sample of 219 goats representing three phenotypic groups. All studied loci were polymorphic, having three morphs for BMP4, LALBA and two morphs for k-CSN3 and GnRHR in the study population. A significant difference between genotypic frequencies for BMP4 and GnRHR genes was found while PIC criterion revealed an intermediate polymorphism for all analyzed phenotypic groups except for k-CSN3 and GnRHR genes. Cross-bred animals for BMP4 gene and nondescript animals for LALBA gene were comparatively more polymorphic according to the effective allele number criterion. This study provides insight into the genetic diversity of Sri Lankan goats, which can be utilized to develop single nucleotide polymorphism markers to be used in association studies, and marker assisted selection.Int J Appl Sci Biotechnol, Vol 4(1): 133-138